The Role of Dreaming in Affect Regulation - Zeilinga, Abraham Dirk (Department of Psychology, 2023)
Research investigating the change in affect across sleep focuses on the association between sleep physiology and affect regulation and often do not consider the contribution of dreaming mentation to affect regulatory processes. The aim of this study was to investigate whether dreaming regulates affect by examining the change in affect within dreams and between dreams elicited during different timepoints in the night. The hypotheses were that if dreams are responsible for affect regulation, there will be a change in self-reported emotion within a dream, leading to less emotionality towards the end of a dream, as well as across the night - leading to less emotionality towards the end of the night. Furthermore, I hypothesized that these within-dream and between-dream changes will be associated with pre-sleep to post sleep change in affect. Healthy students (N = 24; age range 19 – 34 years) spent three non-consecutive nights at a sleep laboratory for PSG monitoring, collection of dream-reports and self-reported dream affect rating. Participants completed an adaptation night followed by two experimental nights. During the first experimental night participants were awoken in Rapid Eye Movement (REM) sleep during the early night (dream-point: Early REM) and on the second experimental night they were awoken in REM sleep towards the end of the night (dream point: Late REM) to record their dreams using voice recordings and collect self-reported dream emotions using Visual Analogue Mood Scales (VAMS). Participants completed mood scales for emotions experienced in both the first part (1st dream-half) and last part (2nd dream half) of their dream. Recorded dreams were transcribed and assessed for affective word content using the Linguistic Inquiry and Word Count program (LIWC). Furthermore, participants rated their mood before and after sleep using the Positive and Negative Affect Schedule (PANAS). A mixed design ANOVA, with dream-half (1st versus 2nd dream-half), dream-point (1st versus 2nd half of the night) and valence (positive versus negative) as factors, was conducted on self-report dream affect ratings. The data showed a significant interaction between dream-half and dream-point, indicating a decline in emotionality from the first half to the second half of early REM dreams, followed by an increase in emotionality from the first to the second half of late REM dream, although still below that of early REM levels. A similar analysis of affective words reported in the dreams showed significant decrease in objectively scored emotional content of dreams from early to late REM. However, there was no association between change in dream affect and change in mood, possibly because participants had little variation in their mood. These results suggest that there are fluctuations in dream affect during the night, which settle at a point between high initial dream affect and low late dream affect, which speculatively represents an emotional homeostatic settling point that allows for next-day readiness. This change towards a speculated homeostatic point and the overall attenuation of dream affect across the night, support the notion that dreaming plays a role in affect regulation.